IGF1 affects macrophage invasion and activation and TNF-α production in the sciatic nerves of female SOD1G93A mice. (6th March 2018) - Ji, Yingxiao; Duan, Weisong; Liu, Yaling; Liu, Yakun; Liu, Chang; Li, Yuanyuan; Wen, Di; Li, Zhongyao; Li, Chunyan
Highlights: IGF1 treatment alleviates inflammation in the sciatic nerve of ALS mice. IGF1 knockdown aggravates inflammation in the sciatic nerve of ALS mice. Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease leading to paralysis and death within 3–5 years of its diagnosis. The SOD1G93A mouse is used extensively as an ALS animal model. Increasing evidence shows that non-neuronal cellscontribute to the pathogenesis and progression of ALS. Among them, many studies focus on microgliosis in the spinal cord (SC); while few on macrophage activation in the sciatic nerves. Substantial evidence shows that insulin-like growth factor 1 (IGF1) delays disease progression and increases the lifespan of SOD1G93A mice, and some studies indicate that IGF1 reduces inflammation in the SC of ALS mice. However, no studies have focused on the effect of IGF on sciatic nerve inflammation. Here, we find that ALS progression is characterized by increasing macrophage invasion and activation accompanied by significant TNF-α production in the sciatic nerve. Furthermore, IGF1 treatment and knockdown alleviate and aggravate these responses, respectively. Collectively, our findings show the first time that IGF1 has an anti-inflammatory effect in the sciatic nerves of SOD1G93A mice.